Renal juxtaglomerular cell tumor with normal renin activity and potassium level: a case report - Yoko Kohno; Satoshi Nitta; Kozaburo Tanuma; Masanobu Shiga; Yoshiyuki Nagumo; Shuya Kandori; Takashi Kawahara; Akio Hoshi; Hiromitsu Negoro; Bryan J. Mathis; Hitomi Kawai; Yoji Nagashima; et al. (Journal of Medical Case Reports)
Abstract Background Benign and rare renal juxtaglomerular cell tumor produces renin, leading to secondary hyperaldosteronism. Typical clinical features include hypertension, elevated renin activity, hyperaldosteronism, and hypokalemia. Herein, we present a unique and enlightening case of juxtaglomerular cell tumor with hypertension, with normal renin activity and potassium levels. Case presentation A 39-year-old Sri Lankan man with a personal history of uncontrollable hypertension was admitted to our hospital for a right renal mass on ultrasound. Dynamic contrast-enhanced computed tomography and magnetic resonance imaging showed a 20-mm mass in the cortex of the right kidney. The preoperative diagnosis was nonclear cell renal cell carcinoma on the basis of both radiological findings, but a 10-mm mass was also found in the bilateral adrenal gland. Although plasma renin activity was normal while plasma aldosterone concentration was elevated at the upright position, primary aldosteronism (plasma aldosterone concentration/plasma renin activity ratio above 200) was not present. Partial nephrectomy of the tumor led to remission of hypertension and hyperaldosteronism. The patient was diagnosed with juxtaglomerular cell tumor on the basis of immunohistological findings. Conclusion We coincidentally conducted the hormonal tests owing to the small adrenal mass. Hormonal testing should be conducted in patients with both uncontrollable or juvenile hypertension and renal masses and, regardless of plasma renin activity, the preoperative diagnosis of juxtaglomerular cell tumor should not be ruled out in such patients.